Using fluorescence in minimally invasive thoracic surgery: a narrative review - Pohlman, Alexander; Hallare, Jericho; Abdelsattar, Zaid M. (Video-Assisted Thoracic Surgery, 2026)
Background and Objective: Fluorescence imaging has an increasing number of uses in minimally invasive thoracic surgery. Indocyanine green (ICG) is the primary agent used given its safe pharmacologic profile and ability to seamlessly integrate into minimally invasive platforms. However, other agents and combinations of technology exist. In this context, we aim to highlight fluorescence technology and detail its reported uses and future directions in the evolving world of minimally invasive thoracic surgery.Methods: We used medical subject headings (MeSH) terms “fluorescence imaging” AND “thoracic surgery” and “indocyanine green” AND “thoracic surgery” in PubMed and limited our search to articles available in English, revealing a total of 160 original publications in the last fifteen years encompassing a broad set of study designs and uses.Key Content and Findings: ICG uses near-infrared fluorescence to illuminate any structure it is injected into. In most cases this is done via intravenous injection to identify major vessels or parenchyma that those vessels supply. However, there are other unique uses in thoracic surgery, such as identification of the thoracic duct (TD) via lymphatic injection, airways via aerosolization and injection into bronchi, or injection directly into interstitial spaces. Improvements in identification of airways, lymphatics, and vessels allows for safe intra-operative navigation, while also improving accuracy in cancer resections and nodal yield. Sub-lobar resections are becoming increasingly utilized for lung cancer, so fluorescence-guided localization can help identify nodules that are not palpable or identify specific lung segments for resection. Injection into airways can help with dissection during pulmonary and esophageal resections, while injection into lymphatics can help minimize injuries to the TD intra-operatively and localize TD injuries when complications do arise.Conclusions: Overall, fluorescence imaging provides a safe and effective means of improving accuracy and safety in a variety of intra-thoracic procedures. Adoption is likely to increase in the coming years as use of minimally invasive, and particularly robotic-assisted surgery, increases.